2020
DOI: 10.1155/2020/7401045
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Health Technologies May Be Acceptable Tools for Providing Social Support to Tuberculosis Patients in Rural Uganda: A Parallel Mixed-Method Study

Abstract: Background. Social support has been shown to mitigate social barriers to medication adherence and improve tuberculosis (TB) treatment success rates. The use of mobile technology to activate social support systems among TB patients, however, has not been well explored. Moreover, studies that tie supportive SMS (Short Message Service) texts to electronic monitoring of TB medication adherence are lacking. Objective. To explore TB patients’ current access to social support and perceptions of utilizing real-time ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 25 publications
0
22
0
2
Order By: Relevance
“…More generally, several systematic reviews have shown that there is substantial evidence for the utility of mobile phone reminders to improve antiretroviral therapy adherence for people living with HIV in East Africa [ 14 , 15 ]. Studies in Uganda suggest that SMS text messaging is also a feasible and acceptable platform to support tuberculosis medication adherence [ 16 , 17 ] and testing [ 18 , 19 ]. Given the rapid rise in mobile phone ownership and the types of phones available and the importance of tailored interventions, there is a pressing need to examine the current state of mobile phones among AYAs in East Africa.…”
Section: Introductionmentioning
confidence: 99%
“…More generally, several systematic reviews have shown that there is substantial evidence for the utility of mobile phone reminders to improve antiretroviral therapy adherence for people living with HIV in East Africa [ 14 , 15 ]. Studies in Uganda suggest that SMS text messaging is also a feasible and acceptable platform to support tuberculosis medication adherence [ 16 , 17 ] and testing [ 18 , 19 ]. Given the rapid rise in mobile phone ownership and the types of phones available and the importance of tailored interventions, there is a pressing need to examine the current state of mobile phones among AYAs in East Africa.…”
Section: Introductionmentioning
confidence: 99%
“…The use of mobile health technologies (e.g., smartphone apps, text messages, wearable devices) in supporting tuberculosis care is highly recommended by the World Health Organization as an emerging opportunity that can close the gaps in tuberculosis care (World Health Organization, 2019). Although their application in tuberculosis care in developing countries is still in its infancy, there is some evidence that they can enhance tuberculosis care through screening and case notification (Tumuhimbise & Musiimenta, 2021a), motivating treatment adherence (Musiimenta et al, 2018(Musiimenta et al, , 2019, fostering prenatal service utilization (Musiimenta et al, 2020a(Musiimenta et al, , b, 2021Tumuhimbise et al, 2020), and providing social support to tuberculosis patients (Musiimenta et al, 2020a, b). Mobile health technologies are low-cost applications that can potentially be sensitive to both the private sector ways of working and the expectations of the national tuberculosis programs (Uplekar, 2016), with the ability to produce tremendous results in facilitating the engagement of the private hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…According to research conducted in Uganda, the use of smartphones as a communication medium provides different social support, namely by providing emotional support, instrumental support, and information via smartphones, besides notifications on smartphones can provide motivation in treatment adherence by creating a sense of obligation to tuberculosis patients to drink. medicine regularly and on time (Musiimenta et al, 2020). In addition to providing support in the form of health information and providing emotional support that will help patients cope with stress, nurses also have a role in providing information and working with the patient's family to monitor taking medication (Munali, Kusnanto, Hanik Endang Nihayati, Hidayat Arifin, 2019).…”
Section: Discussionmentioning
confidence: 99%